Modern Society Challenges: Youth Communication in Instagram - Markivska, Liudmyla L.; Siruk, Natalia M.; Durmanenko, Oksana L.; Redchuk, Rymma O.; Tarasyuk, Liudmyla M. (International Journal of Criminology and Sociology, 2021)
With the emergence and further development of network communication, the number of participants in this process began to increase. The youth turned out to be especially receptive and open to such modern manifestations of communication. It is the youth who actively and easily joins the use of social networks in their lives, where they mainly work. The article is devoted to the consideration of the main theoretical and research approaches to the problem of modern challenges of society - communication of young people on Instagram. The authors noted that one of the main signs of the development of modern society is the rapid formation of computer information technologies, which gives a modern person an opportunity to study, discuss problems that bother him, meet new people and communicate with friends, use the unlimited possibilities of the Internet. One of such information media is the social youth network - Instagram, which can be called one of the best, most convenient and interesting. The article notes that it is young people who master network communication better and use it more often than other age groups, because they are at the forefront of new transformations, and therefore the study of their communicative practices seems to be the most significant and promising.